Aluminum-based material for use in hydrogen cartridges of the hydrogen fuel cell supply system - A. I. Nizovskii; S. V. Belkova; L. O. Shtripling (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
Materials have been developed for hydrogen cartridges using the reaction of activated massive commercial aluminum alloys with water as a hydrogen source. A wide range of industrial aluminum alloys, including secondary aluminum, as well as compacted chips, can be used as starting aluminum materials. It has been shown that activated products are stable for a long time when stored in dry conditions. Prolonged exposure to water vapor leads to loss of reactivity.